Dukungan Lembaga dan Tingkat Partisipasi Petani dalam Keberlanjutan Usahatani Padi Sehat di Desa Rejo Asri - Helvi Yanfika; Indah Nurmayasari; Kordiyana K. Rangga; Fifi Silviana (Jurnal Penyuluhan, 2023)
The success of rice farming which has high productivity and is able to meet people's food needs is largely determined by farmers as business actors. The behavior of farmers in farming is not only related to cultivation efforts, but also includes the contribution of farmers in group institutions which hopefully provide a lot of support for rice farming activities. The aims of this study are: 1) analyzing the institutional support for farmer participation. 2) analyzing the participation of healthy rice farmers. 3) analyzing the sustainability of healthy rice farming. 4) analyzing the institutional support for the level of farmer participation. 5) analyzing the effect of farmer participation level on the sustainability of healthy rice farming in Rejo Asri Village, Seputih Raman District, Central Lampung Regency. This study uses survey method with the respondents in this study amounted to 50 healthy rice farmers. The research location was chosen purposively and used quantitative descriptive analysis methods with Multiple Linear Regression Test and Simple Linear Regression Test. The results showed that the role of the extension agent affected farmer participation, while the indicators of the leadership of the farmer group leader and access to information did not affect the participation of healthy rice farmers. The second objective shows that the level of farmer participation at the planning stage is included in the moderately participating category, at the implementation, benefit-taking, and evaluation stages are included in the very participating category. The third objective of the sustainability of healthy rice farming in this study is included in the very sustainable category. The fourth objective shows that the role of the extension worker affects the level of farmer participation, while the indicators of the leadership of farmer group leaders and access to information do not affect the level of participation of healthy rice farmers. The fifth objective is the influence of the level of farmer participation on the sustainability of healthy rice farming in Rejo Asri Village, Seputih Raman District, Central Lampung Regency with an r-square value of 0.553.